Office administration services based on local wisdom - Didin Didin (Universitas Negeri Makassar, 2022)
Modern office administration services are a demand in today's digital transformation era. However, each region has different customs or cultures according to their local wisdom. Therefore, a true administrator figure is able to adapt in order to realize service excellence to service recipients in both the business and public sectors. Experts have adjusted office administration services through 5 (five) functions such as: 1) Managerial Functions, 2) Interpersonal, 3) Technical, 4) Routine, and Analysis or in other words the PARTNER function.